Genotypic And Phenotypic Correlation And Path Analysis In Durum Wheat (Triticum turgidum L. var. durum) (Bangladesh Journal of Agricultural Research, 2013)
An experiment was conducted at Regional Agricultural Research Station, Ishurdi during the 2009-10 cropping season with the objective of estimating the associations between yield and yield-related traits and to identify direct and indirect effects of characters on grain yield in durum wheat. The result showed significant variation among the genotypes for all the characters studied. Significant positive correlation was found for plant height, number of spikes/m2 and 1000-grain weight with grain yield. Heading days and maturity days showed negative correlation with grain yield. Maturity days, number of spikes/m2 and 1000-grain weight had significant positive direct effects on grain yield. Number of grains/spike had also direct positive effect, but in low magnitude. The indirect effect of heading days and plant height on grain yield was found mainly through maturity days and 1000-grain weight. It can be concluded that emphasis should be given on heading days and plant height along with 1000-grain weight, number of spikes/m2 and number of grains/spike for selection of durum wheat genotypes. Bangladesh J. Agril. Res. 38(2): 219-225, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15885